2021
DOI: 10.1111/bju.15346
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the use of neoadjuvant chemotherapy and oncological outcomes for high‐risk upper tract urothelial carcinoma: a multicentre retrospective study

Abstract: To evaluate temporal trends in neoadjuvant chemotherapy (NAC) utilisation and outcomes in patients with locally advanced upper tract urothelial carcinoma (UTUC). Patients and MethodsWe included 289 patients from seven hospitals who underwent radical nephroureterectomy (RNU) for locally advanced UTUC (≥cT3 or cN+) between 2000 and 2020. These patients received RNU alone or two to four courses of NAC with either a cisplatin-or carboplatin-based regimen. We evaluated the temporal changes in NAC use and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Of the inclusion criteria of those phase III studies, the patient's lymphovascular invasion (LVI) status was not included in the definition of high-risk disease. Because LVI status is one of the established pathological risk factors for poor prognosis in patients with UC, [13][14][15][16][17][18][19] we hypothesize that it might play a key role in the selection of potential candidates for adjuvant immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the inclusion criteria of those phase III studies, the patient's lymphovascular invasion (LVI) status was not included in the definition of high-risk disease. Because LVI status is one of the established pathological risk factors for poor prognosis in patients with UC, [13][14][15][16][17][18][19] we hypothesize that it might play a key role in the selection of potential candidates for adjuvant immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Of the inclusion criteria of those phase III studies, the patient's lymphovascular invasion (LVI) status was not included in the definition of high‐risk disease. Because LVI status is one of the established pathological risk factors for poor prognosis in patients with UC, 13 , 14 , 15 , 16 , 17 , 18 , 19 we hypothesize that it might play a key role in the selection of potential candidates for adjuvant immunotherapy. Firstly, we evaluate the effect of trial eligibility for adjuvant immunotherapy on prognosis in patients with localized and locally advanced muscle‐invasive bladder carcinoma (MIBC) and upper tract urothelial carcinoma (UTUC) in a real‐world practice.…”
Section: Introductionmentioning
confidence: 99%
“…This very low number is discordant as to what is being recently reported from other experiences in other countries. Japanese data from Hamaya et al [21], reported a significantly increased use of NAC for high-risk UTUC after 2010 from a baseline of 19% (2006)(2007)(2008)(2009)(2010), to 58% from 2011-2015, and to 79% from 2016-2020. Also, we were able to model NAC influence in relation to perioperative outcomes which in the future should be evaluated in the patient-and tumor-related decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable Cox regression analysis was conducted to investigate the effect of upfront intensive therapy after adjusting for potential confounders using a propensity score-based inverse probability of treatment weighting (IPTW) method to adjust for group imbalances in the oncological outcomes. 29,30 HRs with 95% CIs were calculated after controlling for potential confounders for upfront therapy, including patient age, ECOG PS, Gleason score, EOD. P values < 0.05 were considered statistically signi cant.…”
Section: Discussionmentioning
confidence: 99%